Different Effects between Trigeminal Sensory and Vagal Visceral Input on Salivary Gland Blood Flow - Ramadhani, Ratna; Sato, Toshiya; Ishii, Hisayoshi (Journal of Dentistry Indonesia, 2025)
Objective: The purpose of the present study was to evaluate the different effects of trigeminal sensory and vagal-visceral inputs on blood flow (BF) in the submandibular gland (SMG). Methods: Ten to eleven-week-old Wistar rats were anesthetized with urethane (1.0 g/kg) and artificially ventilated. The femoral artery was cannulated for systemic arterial blood pressure (SABP) measurement. The cervical sympathetic trunk (CST) on both sides and the cervical vagus nerve (CVN) on the right side were cut before the stimulation of the left abdominal vagus nerve (AVN). The CVN and lingual nerve (LN) were stimulated after cutting the CST and CVN. AVN, LN, and CVN were electrically stimulated with supramaximal intensity (20 V, 20 Hz, 2-ms duration) for 20 s. SMG hemodynamics were recorded using a laser speckle imaging blood flow meter. SABP was recorded using a Statham pressure transducer. Results: LN stimulation elicited an increase in both SABP and SMG BF. On the other hand, CVN and AVN stimulation induced an increase in SABP and SMG BF. However, the SMG BF increase was lower than that observed after LN stimulation. Conclusion: Trigeminal sensory input rather than vagal-visceral input appears to be involved in the regulation of SMG BF.